Medicinal plants in the treatment of urinary tract malignancies during the Araboislamic period (7th- 14th century AD). Issue 4 (2nd October 2022) - Drogosis, Achillefs; Mamoulakis, Charalampos; Chrysos, Emmanuel; Tsoucalas, Gregory; Michaleas, Spyros N.; Karamanou, Marianna
ABSTRACT: Arabic medicine, or Arab-Islamic, mainly refers to all developments achieved in the Age of Khalifs, or the Golden Age of the Arab-Islamic civilization (ca 7 th -14 th centuries AD). Arab scholars adopted ancient Greek medicine and soon understood the essence of the fatal disease known as cancer. They introduced various new types of cancer, distinguishing other entities like infection and proposed new methods of treatment, both surgical and non-invasive. Herbal medicine after Dioscurides and Galen bloomed in the Arabic world. Malignancy of the urinary tract was identified and a plethora of herbs were used to slow down its expansion. Moreover, herbal drugs were introduced to alleviate cancerous symptomatology. Avicenna introduced Hindiba, while known scholars like Abulcasis and Rhazes noted the benefits of garlic, onion, black seeds, pomegranate, olive oil as well as leaf and bread wheat. Arabian herbal medicine may still be beneficial in anticancer fight and mainly in the palliative medicine. It should be emphasized that almost 50% of the drugs administered today have their point of origin in the plants used in antiquity.